Toothbrushing behavior in children – an observational study of toothbrushing performance in 12 year olds - Renate Deinzer; Oliver Cordes; Julia Weber; Lisa Hassebrauck; Ulrike Weik; Norbert Krämer; Klaus Pieper; Jutta Margraf-Stiksrud (BMC Oral Health, 2019)
Abstract Background Many countries offer systematic group prevention programs in kindergarten and school in order to promote children’s oral health. Little is known, however, about the actual toothbrushing abilities of children when group prevention programs end. Methods In Germany, all children take advantage from a nationwide group prevention program (called “Gruppenprophylaxe”) lasting from kindergarten up to sixth grade (12 years of age). Standardized recommendations are given concerning brushing systematics and brushing movements. N = 174 children at the age of 12 were thus randomly selected from two German towns and were asked to perform toothbrushing to the best of their abilities in front of a mirror which also served as a camera. Brushing behavior was analyzed by video analysis. Results Children brushed their teeth for an average of 200 s ± 80.48 s (mean ± SD). Still, more than 55% missed at least one sextant when brushing inner surfaces, 16% missed them all. Only 7.5% of the children brushed both inner and outer surfaces by the intended movements (vertical movements on the inner surfaces and circular movements on the outer surfaces) for at least 90% of the respective brushing time. Instead, horizontal brushing was very common on the lateral surfaces. Conclusions The present analysis indicates that children have low efficiency to adopt the tooth-brushing recommendations given in prevention programs. This is surprising as great endeavors are made to help children internalize the recommendations. Future research is needed to better understand which factors impede adoption of toothbrushing recommendations in children and which efforts are necessary to improve their toothbrushing abilities.